Detection and miss rates of autofluorescence imaging of adenomatous and polypoid lesions during colonoscopy: a systematic review and meta-analysis - Zhao, Zi-Ye; Guan, Yu-Gen; Li, Bai-Rong; Shan, Yong-Qi; Yan, Fei-Hu; Gao, Yong-Jun-Yi; Wang, Hao; Lou, Zheng; Fu, Chuang-Gang; Yu, En-Da (Endoscopy International Open, 2015)
Backgroundand study aims: Autofluorescence imaging (AFI) is an endoscopic imaging technique used to increase the detection of premalignant gastrointestinal lesions, and it has gradually become popular in recent years. This meta-analysis was performed to examine whether AFI provides greater efficacy in the detection of adenomatous and polypoid lesions and can even prevent the failure to detect a single adenoma or polyp. The aim of the study was to systematically review the efficacy of AFI in increasing detection rates and decreasing miss rates.Methods: Pertinent articles were identified through a search of databases up to December 2013 that included patients who had undergone two same-day colonoscopies (AFI and white light endoscopy [WLE]), followed by polypectomy. Fixed and random effects models were used to detect significant differences between AFI and WLE in regard to adenoma detection rate (ADR), polyp detection rate (PDR), adenoma miss rate (AMR), polyp miss rate (PMR), and procedural time.Results: A total of 1199 patients from six eligible studies met the inclusion criteria. No significant differences were found in ADR (odds ratio [OR] 1.01; 95 % confidence interval [95 %CI] 0.74 – 1.37), PDR (OR 0.86; 95 %CI 0.57 – 1.30), or advanced ADR (OR 1.22; 95 %CI 0.69 – 2.17). The AMR (OR 0.62; 95 %CI 0.44 – 0.86) and PMR (OR 0.64; 95 %CI 0.48 – 0.85) by AFI were significantly lower than those by WLE. The procedural time of AFI was significantly longer than that of WLE (mean 8.00 minutes; 95 %CI 1.59 – 14.41). Subgroup meta-analysis for the other characteristics was not performed because of insufficiency of the primary data. Conclusions: AFI decreases AMR and PMR significantly compared with WLE but does not improve ADR or PDR. AMR and PMR may be decreased by using AFI in flat and small lesions or when less experienced endoscopists perform the procedure.